First Nations men hand drumming on stage in 1975 - Mariposa Folk Foundation (1975)
Title based on content of image. First Nations men hand drumming on the Native Peoples Area stage. Annotations include: "DW 75. (2)" Slide number 12. Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.